(untitled) (Journal of the College of Basic Education, 2023)
The researcher chose this topic, which deals with the methods of preparing the Hungarian actor academically during the period between 1920 and 1949 AD, because of the advantages and qualities he possessed that shed light - when studied and analyzed - on the crystallization of the local features in which the process of development became evident in the preparation of the theatrical actor professionally and the possibility of benefiting from them in preparing Contemporary Iraqi theater actor.